Associations between visual skills and serve reception performance in elite male volleyball outside hitters - Dong, X.; Gao, D.; Gao, Y.; Han, L.; Zhou, X.; Weng, C.; Wang, J.; Wang, Q.; Xiao, Y.; Wang, Q.; Tang, Y. (Frontiers in Physiology, 2026)
Introduction: Visual skills are considered important for elite athletic performance, but their association with volleyball-specific performance remains unclear. This study examined the associations between visual skills and match-based serve reception performance in elite male volleyball outside hitters.